Never Give Up Attitude in the Novel of Negeri 5 Menara as A Reinforcement of the Pancasila Student Profile - Darmiyati; Mukti Widayati; Nurnaningsih Nurnaningsih (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This qualitative study explores the depiction of the "never give up" attitude in Ahmad Fuadi's novel "Negeri 5 Menara," focusing on its role in reinforcing the Pancasila student profile. Utilizing a methodological framework grounded in theoretical sources, the research conducts an in-depth investigation employing literature review, analysis, and presentation techniques. Data collection methods include library research and meticulous note-taking, with a structured strategy centered on focused inquiry and single case studies. Semiotic analysis is employed to uncover layers of meaning within the text, with data validation conducted through theoretical triangulation. The findings highlight the portrayal of the never give up attitude as the characters' relentless pursuit of success, influenced by their experiences at Pesantren Madani. Key principles shaping this attitude are identified, including "man jadda wajada" (Whoever strives will succeed) and "Iâ€™timadu alÄ nafsik" (Stand on your own feet). In conclusion, the study emphasizes the significance of the never-give-up attitude in fortifying the Pancasila student profile, fostering resilience and determination. It underscores the intricate interplay between literary portrayal and societal values, offering insights for educators and scholars.